Marketing Strategy in Event Sponsorship and Social Media of PT Telkomsel Surabaya - Maulida, Assyaffa; Nugroho , Rusdi Hidayat (Business and Investment Review, 2025)
This study explores the marketing strategies employed by PT Telkomsel Surabaya through event sponsorship and social media platforms. Amidst increasing competition in the telecommunications industry, the integration of offline and online marketing strategies becomes essential to maintain brand relevance and consumer loyalty. Event sponsorship aims to enhance brand image and foster direct engagement with consumers, while social media serves as a platform to expand market reach and facilitate interactive communication. Using a qualitative case study approach, this research combines data from interviews, observations, and social media content analysis. The findings reveal that Telkomsel's collaboration with local events successfully boosts brand awareness and strengthens its community-oriented image. Meanwhile, the strategic use of Instagram and TikTok fosters customer loyalty through engaging and dynamic content. This study highlights the importance of synergizing event sponsorship and social media strategies to achieve effective marketing outcomes. Practical implications are provided for companies to innovate in their marketing efforts and adapt to evolving consumer behaviors.